Low toxicity antisolvent synthesis of composition-tunable luminescent all-inorganic perovskite nanocrystals. Issue 15 (15th October 2018) - Li, Wen; Deng, Wen; Fan, Xiaoqiang; Chun, Fengjun; Xie, Meilin; Luo, Chao; Yang, Shiyu; Osman, Hanan; Liu, Chuanqi; Zheng, Xiaotong; Yang, Weiqing
Abstract: All-inorganic perovskite nanocrystals have held great promise as incredibly effective luminescent materials and also have been synthesized efficiently by room temperature approaches. Toluene, a high toxicity solvent, is often used as a valid antisolvent in ligand-assisted reprecipitation strategy, which badly restricts the commercial application of this convenient method. Here, aiming to address the toluene toxicity issue, the low toxic tetraethyl orthosilicate (TEOS) is employed as a new alternative antisolvent to achieve high uniform and composition dependent luminescent all-inorganic perovskite Cs4 PbX6 (X = I, Br, Cl) combined with CsPbX3 (X = I, Br, Cl) nanocrystals with tunable emission large-span wavelengths (626–437 nm) and remarkably narrow full width at half-maximum (FWHM) monochromaticity (down to 19 nm). Meanwhile, the ratio of CsBr to PbBr2 is proved to be a critical factor to control the crystalline phase of the resulting perovskite nanocrystals. Additionally, one monochromatic light-emitting diode (LED) lamp with brightly pure green emission is fabricated based on bromine-based perovskite nanocrystals. This newly developed low toxicity antisolvent synthesis (LTaS) is suitable candidate for commercial production in an environmentally-friendly way, and the as-obtained perovskite materials with superior optical merits will be brought to the forefront of lighting and displays.